Winning a district election in a clientelistic society: Evidence from decentralized Indonesia - Alfa Farah (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2019)
Lower-level officials often engage in clientelistic relations with the upper-level government. The nature of these relations might be determined by institutional factors such as how the lower-level officials come into their position. This paper specifically highlights the different political incentives that elected versus appointed lower-level officials have for becoming political intermediaries for the upper-level government, and it investigates empirically how these differing incentives bring electoral consequences. Upon exploiting a natural experiment in Indonesia, the study found that the elected village headmen have stronger incentives to support the incumbent mayor than the appointed village headmen do. The results suggest that while civil service reforms might weaken the bureaucratic clientelism, the pre-existing patronclient relations that are deeply embedded in the society are immersed in local political competitions; thus, this practice challenges political consolidation in the young democracy.
Keywords: D72; H77; H83; O17; O18; 330; clientelism; selection mechanism; local elections